The Implementation of the Going Concern Principle in Bankruptcy and The Suspension of Payment to Protect the Economic Rights of the Parties - Elisatris Gultom; Huta Disyon (Faculty of Law, Universitas Padjadjaran, 2022)
This study aims to analyze the regulation on the going concern principle and indicators to determine the continuity of prospective business activity. It employed normative juridical method that was based on library research. It obtained secondary data sourced from primary, secondary, and tertiary legal materials. The study was analytical descriptive because the author described the going concern principle by referring to the Law Number 37 of 2004 on Bankruptcy and Suspension of Debt Payment Obligations (the Bankruptcy Law). subsequently, the study analyzed it to find relevant indicators to determine whether a prospective business activity can continue or not. The data were analyzed using a qualitative juridical method. The results indicate that the sustainability of the debtor’s business is crucial for the fulfillment of the economic rights of the debtor and creditor, even though the law does not provide indicators to determine that the prospective debtor’s business will continue. For this reason, decisions regarding the business continuity of debtors are influenced by various internal and external factors and must be made by competent parties.DOI: https://doi.org/10.22304/pjih.v9n3.a3